The Role of Long Noncoding RNAs in the Epigenetic Control of Gene Expression. Issue 3 (2nd February 2014) - Morlando, Mariangela; Ballarino, Monica; Fatica, Alessandro; Bozzoni, Irene
Abstract Recent advances in the methodologies employed to deeply analyse the complexity of transcriptomes have unveiled the existence of a new class of transcripts, long noncoding RNAs (lncRNAs). A significant amount of effort has been dedicated to the study of lncRNAs, and a large body of evidence now exists indicating their relevant role in different regulatory steps of gene expression. Given the role of epigenetics in disease development and progression, this Minireview focuses on lncRNAs involved in epigenetic control and provides an overview of the mechanisms used to guide epigenetic‐modifying complexes to adjacent (cis‐acting) or independent (trans‐acting) genomic loci. Furthermore, it describes the activities of these transcripts in controlling the formation and spreading of heterochromatin domains. Just as other RNA molecules have found therapeutic application, though much remains to be elucidated about the structure and function of these lncRNAs, they too could hold potential as biomarkers, targets, and therapeutic agents.